Existence and Convergence of Solutions to Fractional Pure Critical Exponent Problems - Hernández-Santamaría Víctor; Saldaña Alberto (Advanced Nonlinear Studies, 2021)
We study existence and convergence properties of least-energy symmetric solutions (l.e.s.s.) to the pure critical exponent problem